(untitled) (Comprehensive Journal of Science, 2026)
Financial Technology (FinTech) has transformed the banking industry by enhancing service efficiency, accessibility, and customer experience through digital innovations such as mobile banking, electronic payments, and online financial services. However, limited empirical research has examined whether FinTech adoption improves customer satisfaction in fragile and under-researched economies such as Libya. Therefore, this study investigates the impact of FinTech adoption on customer satisfaction in Libyan banks. FinTech adoption was conceptualized through three dimensions: ease of use, security, and convenience. A quantitative research approach was employed using a structured questionnaire distributed to customers of selected Libyan banks. A total of 384 valid responses were collected and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS software. The results indicate that FinTech adoption has a significant positive effect on customer satisfaction. Convenience was identified as the strongest predictor, followed by ease of use, both of which significantly enhanced customer satisfaction. In contrast, security did not show a significant direct effect. The model demonstrated high explanatory power, indicating that the selected factors account for a substantial proportion of customer satisfaction. This study contributes to the literature by extending FinTech research to the Libyan context and highlighting the importance of functional service benefits in emerging markets. Practically, the findings suggest that banks should prioritize convenient and user-friendly digital services while continuing to strengthen digital transformation strategies.